Extracellular Vesicles as Natural, Safe and Efficient Drug Delivery Systems - Federico Villa; Rodolfo Quarto; Roberta Tasso (MDPI AG, 2019)
Extracellular vesicles (EVs) are particles naturally released from cells, delimited by a lipid bilayer, carrying functionally active biological molecules. In addition to their physiological role in cellular communication, the interest of the scientific community has recently turned to the use of EVs as vehicles for delivering therapeutic molecules. Several attempts are being made to ameliorate drug encapsulation and targeting, but these efforts are thwarted if the starting material does not meet stringent quality criteria. Here, we take a step back to the sources and isolation procedures that could guarantee significant improvements in the purification of EVs to be used as drug carriers, highlighting the advantages and shortcomings of each approach.